STRATEGI SOSIALISASI PENCEGAHAN STUNTING MELALUI PEMANFAATAN COOKIES DAUN KELOR DAN EDUKASI PERNIKAHAN DINI DI KELURAHAN TANJUNG, KECAMATAN LABUHAN HAJI, LOMBOK TIMUR - Aprila, Andi; Jurnal Wicara; Yatari, Baiq; Putri, Alifia; Ristiawati, Serlina; Ramadhan, Muh.; Febriani, Ikma; Aen, Hadratul; Safitri, Rita; Putri, Ni; Praneswari, Salwa (Universitas Mataram, 2025)
Community Service Program (KKN) is one of the forms of student dedication to society, aiming to provide real contributions in addressing local problems. The KKN-PMD program of the University of Mataram, conducted in Tanjung Village, Labuhan Haji Subdistrict, East Lombok Regency, focused on stunting prevention and raising community awareness about the impacts of early marriage. The implementation methods included field surveys, program design, activity implementation, and monitoring and evaluation. The main programs carried out were education on the dangers of early marriage, socialization and distribution of innovative products in the form of moringa leaf cookies as nutritious food, and supplementary feeding (PMT) at the local health posts (posyandu). The results showed an increase in community understanding regarding the importance of children’s nutritional health and the negative impacts of child marriage. The positive response to moringa leaf cookies also indicated that local food innovations can be accepted and have the potential to be developed as a sustainable effort to prevent stunting. Therefore, this KKN activity has made a tangible contribution to creating a healthy and sustainable village.